1994
DOI: 10.1088/0034-4885/57/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic magnetic fields

Abstract: Recent advances in observational techniques reveal the widespread existence of magnetic fields in the Universe, and produce much firmer estimates of magnetic field strengths in interstellar and intergalactic space. Ordered, microgauss-level fields are common in spiral galaxy disks and halos, and appear to be a common property of the intra-cluster medium of clusters of galaces, indeed well beyond the cluster core regions. Strengths of ordered magnetic fields in the intracluster medium of cooling flow clusters e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
1,233
2
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,074 publications
(1,274 citation statements)
references
References 216 publications
33
1,233
2
6
Order By: Relevance
“…The existence, strength and structure of these fields in the intergalactic plane, within the Local Superclusted, has been scrutinized recently [2]. Many spiral galaxies are endowed with coherent magnetic fields of µG (micro Gauss) strength [3,4,5,6,7,8], having approximately the same energy density as the Cosmic Microwave Background Radiation (CMBR). In particular, the field strength of our galaxy is B ≃ 3 × 10 −6 G, similar to that detected in high redshift galaxies [9] and damped Lyman alpha clouds [10].…”
Section: Introductionmentioning
confidence: 99%
“…The existence, strength and structure of these fields in the intergalactic plane, within the Local Superclusted, has been scrutinized recently [2]. Many spiral galaxies are endowed with coherent magnetic fields of µG (micro Gauss) strength [3,4,5,6,7,8], having approximately the same energy density as the Cosmic Microwave Background Radiation (CMBR). In particular, the field strength of our galaxy is B ≃ 3 × 10 −6 G, similar to that detected in high redshift galaxies [9] and damped Lyman alpha clouds [10].…”
Section: Introductionmentioning
confidence: 99%
“…The average field strength is found to be ∼ 3−4 µG. Such a strength corresponds to an approximate energy equipartition between the magnetic field, the cosmic rays confined in the Galaxy, and the small-scale turbulent motion (Kronberg, 1994) …”
Section: Observations Of Magnetic Fieldsmentioning
confidence: 86%
“…For variations of the IGMF and of the density on scales much smaller than c/H 0 , the variance of the rotation measures should increase with the redshift and be detectable for B I G ∼ 6 × 10 −9 G (Kronberg & Perry (1982), Blasi et al (1999)), which is not observed. A strict upper limit of B I G < 10 −9 G can be deduced in such a case (Kronberg (1994)). However such limits need to be revisited with a more accurate description of the large scale structure and taking into account evolutionary effects in intrinsic rotation measures (Kronberg et al (2008)).…”
Section: The Intergalactic Magnetic Fieldmentioning
confidence: 95%
“…In this regard, an astrophysical origin of the IGMF appears as an interesting alternative. A substantial IGMF could be formed later on by ejection of magnetized plasmas into the intergalactic space, from galaxies, AGN, starbursts, Pop III stars and large scale shocks, as discussed for instance by Kronberg (1994), Widrow et al (2012), Ryu et al (2012) and Lilly (2012). For recent overviews on the primordial magnetic field and the IGMF, see for instance reviews by Widrow (2002), Kulsrud & Zweibel (2008), Kandus et al (2011 and Ryu et al (2012).…”
Section: The Intergalactic Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation